Towards understanding the pattern of glacier mass balances in High Mountain Asia using regional climatic modelling - de Kok, Remco J.; Kraaijenbrink, Philip D. A.; Tuinenburg, Obbe A.; Bonekamp, Pleun N. J.; Immerzeel, Walter W. (The Cryosphere, 2020)
Glaciers in High Mountain Asia (HMA) provide an important water resource for communities downstream, and they are markedly impacted by global warming, yet there is a lack of understanding of the observed glacier mass balances and their spatial variability. In particular, the glaciers in the western Kunlun Shan and Karakoram (WKSK) ranges show neutral to positive mass balances despite global warming. Using models of the regional climate and glacier mass balance, we reproduce the observed patterns of glacier mass balance in High Mountain Asia of the last decades within uncertainties. We show that low temperature sensitivities of glaciers and an increase in snowfall, for a large part caused by increases in evapotranspiration from irrigated agriculture, result in positive mass balances in the WKSK. The pattern of mass balances in High Mountain Asia can thus be understood from the combination of changes in climatic forcing and glacier properties, with an important role for irrigated agriculture.